The Future is Written in the Past - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2026)
The essay explores the possibility that the future economy can evolve even without money as a central element of exchange. The author starts from the observation that, historically, money has been the fulcrum of economic exchanges and the development of markets. However, he speculates that a "second market" could emerge in the future, based on mutual trust and solidarity, in which goods are exchanged without the intermediation of money, especially to support those on the margins of society. The current system, based on money, risks entering a phase of stagnation, becoming an obstacle to development. It is therefore proposed to combine the traditional market with an alternative market, without money, where values such as goodwill and social responsibility prevail. This model could help overcome the weakness of the global economy, which is also slowing down due to the rigidity of the monetary system. The author also analyzes recent U.S. political and economic decisions, such as the introduction of tariffs, which have had limited effects on inflation but have slowed global economic growth. He points to the uncertainty of economic forecasts, saying that the future is hardly predictable beyond a few months. The text goes on to analyze GDP growth data in the United States and China, highlighting how the fastest growth is occurring in countries and continents that were previously characterized by weak development, such as Africa, Arabia, Turkey and Southeast Asia. This change suggests a new distribution of development dynamics at the global level. Finally, the essay offers a historical reflection on Europe over the last two centuries, emphasizing how history can repeat itself and how the political and military dynamics of the past can influence the present and the future. The author recalls the Napoleonic era and the Congress of Vienna to highlight the complexity of international relations and the possibility that historical events will be repeated, albeit in different forms. The paper suggests that the future of the economy could be characterized by greater solidarity and social responsibility, with the possibility of combining the traditional market with an alternative market without money. It also stresses the importance of a historical vision for understanding the current and future dynamics of Europe and the world.